AgI-modified TiO2 supported by PAN nanofibers: A heterostructured composite with enhanced visible-light catalytic activity in degrading MO. (October 2016) - Yu, Dandan; Bai, Jie; Liang, Haiou; Ma, Tengfei; Li, Chunping
Abstract: A highly visible-light responsive AgITiO2 /PAN had been successfully synthesized by the electrospinning technique, hydrogenation reduction, solvothermal synthesis, and gas/solid oxidation. The component and morphology of the as-prepared catalysts were characterized by field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), UV–vis diffuse reflectance spectroscopy (DRS), and Fourier transform infrared spectroscopy (FTIR). In the degradation experiments, the as-prepared AgITiO2 /PAN showed a highly photocatalytic activity in degrading methyl orange (MO) under visible light irradiation and the AgI content had a strong effect in their photocatalytic activity. Moreover, the degradation efficiency of MO over AgITiO2 /PAN was much higher as compared to that of pure PAN, AgI/PAN and TiO2 /PAN, which was attributed to the synergistic effect between AgI and TiO2 . Besides, AgITiO2 /PAN had an excellent stability in the cycling tests due to the intimate connect and stable heterostructure of AgITiO2 . It's astonished to find that the application of PAN nanofibers, which presented in membranous form, made it easy separate the catalysts from an aqueous solution without any loss. Highlights: A highly visible-light responsive AgITiO2 /PAN composite had been successfully synthesized. AgITiO2 /PAN were presented in membrane forms, showed a highly photocatalytic activity in degrading MO. The as-prepared composites had an excellent stability and photostability in the photocatalytic cycling tests.